Emission Rate of Particulate Matter and Its Removal Efficiency by Precipitators in Under-Fired Charbroiling Restaurants - Jun-Bok Lee; Ki-Hyun Kim; Heung-Joo Kim; Seog-Ju Cho; Kweon Jung; Shin-Do Kim (The Scientific World Journal)
In order to explore the potent role of meat cooking processes as the emission sources of particulate matter (PM), emission rates and the associated removal efficiency by precipitators were estimated based on the on-site measurements made at five under-fired charbroiling (UFC) restaurants. The emission patterns of PM for these five restaurants were compared after having been sorted into the main meat types used for cooking: beef (B), chicken (C), intestines (I), and pork (P: two sites). The mass concentrations (μg m-3) of three PM fractions (PM2.5/PM10/TSP) measured from these restaurants were 15,510/15,701/17,175 (C); 8,525/10,760/12,676 (B); 11,027/13,249/13,488 (P); and 22,409/22,412/22,414 (I). Emission factors (g kg-1) for those PM fractions were also estimated as 3.23/4.08/4.80 (B), 3.07/3.82/3.87 (P), 8.12/8.22/8.99 (C), and 6.59/6.59/6.59 (I). If the annual emission rate of PM10 is extrapolated by combining its emission factor, population, activity factor, etc., it is estimated as 500 ton year-1, which corresponds to 2.4% of the PM10 budget in Seoul, Korea. Removal efficiencies of PM10 via precipitators, such as an electrostatic precipitator (ESP), bag filter (BF), and the combination system (ESP + catalyst), installed in those UFC restaurants ranged between 54.76 and 98.98%. The removal efficiency of PM by this control system was the least effective for particles with <0.4 μm, although those in the range of 0.4–10 μm were the most effective.